2009
DOI: 10.1128/aem.02182-08
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Campylobacter Bacteria in Air Samples for Continuous Real-Time Monitoring of Campylobacter Colonization in Broiler Flocks

Abstract: Improved monitoring tools are important for the control of Campylobacter bacteria in broiler production. In this study, we compare the sensitivities of detection of Campylobacter by PCR with feces, dust, and air samples during the lifetimes of broilers in two poultry houses and conclude that the sensitivity of detection of Campylobacter in air is comparable to that in other sample materials. Profiling of airborne particles in six poultry houses revealed that the aerodynamic conditions were dependent on the age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 13 publications
1
28
1
3
Order By: Relevance
“…can contaminate food anywhere along the food production process (10), but undercooked poultry is the most important source of infection (3,22,26). Several studies have been carried out on raw food sold by street vendors and in retail outlets (13,16,17,25), but there are few studies that include cooked foods, especially in Mexico (2). In our region and all over northeast Mexico, grilled chicken, bought from both street vendors and retail outlets, is frequently consumed.…”
mentioning
confidence: 99%
“…can contaminate food anywhere along the food production process (10), but undercooked poultry is the most important source of infection (3,22,26). Several studies have been carried out on raw food sold by street vendors and in retail outlets (13,16,17,25), but there are few studies that include cooked foods, especially in Mexico (2). In our region and all over northeast Mexico, grilled chicken, bought from both street vendors and retail outlets, is frequently consumed.…”
mentioning
confidence: 99%
“…In the poultry chain, biotracing has addressed the point of entry of Campylobacter jejuni in the poultry production chain, the impact of processing conditions on the physiology of the organism and modelling the behaviour of Campylobacter along the production chain for the purpose of tracing and tracking contamination (Olsen et al 2009, Gonza Âlez et al 2009). This has resulted in advanced user-friendly tools for source attribution and demonstrated that contamination from the slaughterhouse environment is a significant factor in contaminating chicken meat.…”
Section: Meat Chainmentioning
confidence: 99%
“…The matrix of data generated is the basis for predicting the behaviour of pathogens under given conditions in relevant scenarios (Manios et al 2009, Schvartzman et al 2010b). · There have been developments in novel sampling and sample preparation technologies to overcome existing bottlenecks in end-use analytical laboratories (Olsen et al 2009). · More reliable and faster test systems based on molecular methods have been developed (Josefsen et al 2007, Lo Èfstro Èm et al 2009a, 2009b, Fach et al 2009, Walcher et al 2010.…”
Section: Novel Aspects Of Biotracingmentioning
confidence: 99%
“…While HACCP focuses on the critical production points, biotracing deals with the entire chain, from the primary production at farms (Olsen et al, 2009), through transportation, storage, distribution, shelf-life issues and consumption by consumers. An example here is the biological information on the significance of strains that are isolated during routine quality control checks: does the strain have virulence traits, can it confer pathogenicity, is it recurrent, can it survive the environment of the food production in question?…”
Section: Advantages Of Biotracingmentioning
confidence: 99%